Law and politics of indigenous self-determination: the meaning of the right to prior consultation - Merino, Roger (2019)
Taking as an example the events that occurred during the ‘’Baguazo’’, in this article a profound analysis is made of the social legal situation of the indigenous peoples in Peru. The Law of Prior Consultation, enacted in the Government of Ollanta Humala, is taken as an object of study, and it is argued that this inclusive policy is actually imbued with coloniality, a concept that will be developed throughout the article. Following this line, it is argued that due to the application of Eurocentric concepts in a different context (Latin America), an adverse and counterproductive effect is achieved that leads to a policy of exclusion. Finally, it is proposed as a solution that the State should embrace a different policy, precisely that of promoting and respecting a true self-determination of indigenous peoples.